CYCLING: WHY CITIES ARE GETTING MORE DANGEROUS - Short, John Rennie (Deceleration, 2019)
As cities strive to improve the quality of life for their residents, many are working to promote walking and biking. Such policies make sense, since they can, in the long run, lead to less traffic, cleaner air and healthier people. But the results aren’t all positive, especially in the short to medium term.
Keywords: cycling; quality of life; traffic fatalities; pedestrians